Perkembangan Moral Santri di Madrasah Tahfidz Putri Anak (MTPA) - Nailurrohmah Khoiri; Assya Syahnaz; Febri Widiandari (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2023)
Santri Tahfidz is seen as people of good morals because they have the Al-Qur'an as a controller of their behavior. This study aims to analyze moral development, influencing factors, and Pesantren's efforts to develop the ethical aspects of santri tahfidz at Madrasah Tahfidz Putri Anak (MTPA). The research method used qualitative, data collection techniques through interviews and observations. The process of determining the informants used purposive sampling. This research found three research results. First, the stage of moral development of santri tahfidz at MTPA was the heteronomous stage. Second, the factors that affect the moral development of santri tahfidz were divided into 2, namely, internal factors in the form of nature or nature that has been brought from birth and external factors; the family, the pesantren environment and social relations between friends. Third, the pesantren's efforts in developing the morality aspects of the santri tahfidz were by implementing rules and consequences, as well as several religious and social programs or activities within the pesantren environment.